Pathogenicity and propagation of UPMT27 field isolate of Malaysia fowl adenovirus in chicken embryo liver cells - Salisu, A.; Mat Isa, Nurulfiza; Abdul Razak, Mariatulqabtiah; Bejo, Mohd Hair; Omar, Abdul Rahman; Ideris, Aini (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
The poultry industry in Malaysia is fast growing but has become under threat due to inclusion bodies hepatitis (IBH) caused by strains of fowl adenovirus (FADV). The present study was carried out to propagate a field isolate of FAdV (UPM T27) and examine its pathogenicity in chicken egg embryo and chicken embryo liver cells. Five Specific Pathogen Free (SPF) chicken eggs were inoculated with 0.1mls of the FAdV UPMT27 isolate via chorioallantoic membrane (CAM) sac route. Supernatant from liver homogenate of dead embryo were used to infect freshly prepared chicken embryo liver (CEL) cells and observed for cytopathic effects for serial passages. Subsequently, passage 1 and 2 isolates were stained with H&E and observed under the microscope. Results show 100% mortality of the eggs at 11 days post inoculation and 100% CPE were observed at 4 dpi respectively. Eosinophilic inclusion bodies were also observed in the hepatocyte after H&E staining. These results confirmed that UPMT27 FAdV isolated from Malaysia are highly pathogenic and can be successfully propagated in CEL cells for future studies of the virus.